Caracterização mecânico-metalúrgica de defeitos superficiais em rodas ferroviárias de aços classe C e D AAR - Volponi, Ana Clara Donna (2024)
The increasing demand for higher load capacity and increased railway traffic underscores the need for enhanced studies on wheel defects, which are crucial for the efficiency and safety of railway transportation. To prevent detrimental defects, understanding the damage mechanisms during traffic is essential. By evaluating cast and forged wheels made of AAR class C and D steels, we identified defects such as shelling, wheel flats, spalling, hollow wear, fine flaking, and tread band wear. Hardness measurements along the rim, microhardness in regions close to the surface, and quantitative analyses of inclusions, interlamellar spacing, thicknesses of deformed layers, angles, and sizes of cracks were conducted. Optical and electron microscopy revealed the morphologies of the defects and their interactions with the microstructure. An extensive database was generated, indicating a low influence of manufacturing processes on the genesis of defects but a strong relationship between microhardness, the deformed layer, and surface work hardening. The analysis highlighted the competition between wear and rolling contact fatigue as mechanisms of wheel surface degradation.